Laju Infeksi Penyakit brown band Disease dan Bakteriasosiasi pada Karang acropora sp. di Pulau Barranglompo, Makassar, Sulawesi Selatan - Arniati Massinai (Hasanuddin University, 2016)
Coral diseases more commonly found in tropical regions and is one cause of coral mortality . The purpose of this study was to determine the infection rate of brown band disease on the coral Acropora sp and its bacterial associations.The rate of infection is done by marking the light brown band with a cable tie and then measuring the size of colonies already dead . Colony measurements is done every day for one week .Coral-associated bacterial were isolated by taking a sample of coral infected BrB and inoculated in Marine Agar medium with pour plate method, then purified by zigzag scratch method with a 24 hour incubation. Bacterial identification based on biochemistry assay.The area of coral colonies of Acropora sp who die from the disease BrB were 1.58 to 6.11 cm per day . Coral-associated bacterial identified were Cromobacterium sp, Staphylococcus sp , Flavobacteriun sp and Pseudomonas sp.